2015
DOI: 10.1128/jvi.03432-14
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Genetics System for Severe Fever with Thrombocytopenia Syndrome Virus

Abstract: Severe fever with thrombocytopenia syndrome virus (SFTSV) is an emerging tick-borne pathogen that was first reported in China in 2009. Phylogenetic analysis of the viral genome showed that SFTS virus represents a new lineage within the Phlebovirus genus, distinct from the existing sandfly fever and Uukuniemi virus groups, in the family Bunyaviridae. SFTS disease is characterized by gastrointestinal symptoms, chills, joint pain, myalgia, thrombocytopenia, leukocytopenia, and some hemorrhagic manifestations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 49 publications
1
89
0
1
Order By: Relevance
“…Using SFTSV generated by a reverse-genetic system, Brennan et al showed that the F330S mutation in the M segment was responsible for plaque formation and had a high growth rate in Vero E6 cells (15). The mutation in the GP was detected in the high plaque-forming strain HB29pp, and it was related to Vero E6 cell adaption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using SFTSV generated by a reverse-genetic system, Brennan et al showed that the F330S mutation in the M segment was responsible for plaque formation and had a high growth rate in Vero E6 cells (15). The mutation in the GP was detected in the high plaque-forming strain HB29pp, and it was related to Vero E6 cell adaption.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SFTSV and other genetically related viruses that are pathogenic for humans have been reported in East Asia and North America (8)(9)(10)(11)(12)(13). However, their molecular biological characteristics and pathogenic mechanisms are not fully understood (5,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have shown that NSs is not essential for virus replication but that its absence results in a degree of growth attenuation in cell culture. Recently, we described a reverse-genetics system for pathogenic SFTSV (28). The developed reverse-genetics systems will be useful tools to elucidate the molecular determinants of virulence of the more pathogenic tick-borne phleboviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, UUKV would be a useful comparator to include in studies on the molecular basis of the pathogenesis of STSFV and HRTV in humans. Such investigations will be aided by the availability of reverse-genetics systems that allow specific manipulation of the viral genome, and we have recently established such a system for SFTSV (28). Here, we describe a reverse-genetics system for the recovery of infectious UUKV entirely from cDNA copies of the genome.…”
mentioning
confidence: 99%
“…Generation of viral stocks was performed in Vero76 cells, with titers determined by plaque assay as previously described (18,25). A multiplicity of infection (MOI) of ϳ0.01 was used in all experiments involving virus infection, unless stated otherwise.…”
Section: Methodsmentioning
confidence: 99%